2021
DOI: 10.1186/s12935-021-01881-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential plasma biomarkers in early-stage nasopharyngeal carcinoma-derived exosomes based on RNA sequencing

Abstract: Background Early diagnosis of nasopharyngeal carcinoma (NPC) is vital to improve the prognosis of these patients. However, early diagnosis of NPC is typically challenging. Therefore, we explored the pathogenetic roles and associated mechanisms of exosomes in plasma of patients with early-stage NPC. Methods Exosomes in plasma were extracted by ultra-high-speed centrifugation. Western blot and transmission electron microscopy (TEM) were used to verif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…Similarly, Pu et al (2016) reported that hsa-miR-193a-5p contributes to osteosarcoma metastasis by suppressing SRR expression. Another candidate miRNA, hsa-miR-1301-3p, was upregulated in early-stage nasopharyngeal carcinoma ( Zheng et al, 2021 ). However, no studies have investigated the target genes and mechanisms of both hsa-miR-1301-3p and hsa-miR-193a-5p in the context of UCEC.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Pu et al (2016) reported that hsa-miR-193a-5p contributes to osteosarcoma metastasis by suppressing SRR expression. Another candidate miRNA, hsa-miR-1301-3p, was upregulated in early-stage nasopharyngeal carcinoma ( Zheng et al, 2021 ). However, no studies have investigated the target genes and mechanisms of both hsa-miR-1301-3p and hsa-miR-193a-5p in the context of UCEC.…”
Section: Discussionmentioning
confidence: 99%
“…miR-BART7-3p is a potential prognostic biomarker, whereby prominent levels of pre-treatment miR-BART7-3p in plasma indicated a higher risk of distant metastasis whereas post-treatment miR-BART7-3p is associated with short DMFS and OS ( 191 , 192 ). Significant upregulation of miR-1301-3p was detected in the exosomes from early-stage NPC patients’ plasma, indicating their potential application as diagnostic biomarkers in early-stage NPC ( 193 ).…”
Section: Targeting Tumor Microenvironment In Nasopharyngeal Carcinoma...mentioning
confidence: 99%
“…Exosomes are rich in genetic material and molecules: DNA, miRNA, lncRNAs, proteins and lipids, which are essential for cell-cell communication and physiological status. Moreover, exosomes are also involved in the regulation of tumor progression in the TME ( 11 ). Recently, it has been demonstrated that exosomes secreted by tumor cells play critical roles in cancer progression and invasion, including TME remodeling, tumor metastasis and tumor-associated immunosuppression ( 73 ).…”
Section: Mirnas/lncrnas From Tumor-derived Exosomes Mediate the Funct...mentioning
confidence: 99%
“…Tumor MDSCs are mainly divided into two main subtypes according to their phenotypes and origins, which are defined by cell surface markers of MDSCs in both tumor models and cancer patients ( 10 , 11 ). The phenotypes of MDSCs in tumor-bearing mice are defined using Gr1 (ly6G/ly6C)/CD11b and further include two subtypes of MDSCs: Monocyte-MDSCs (M-MDSCs, CD11b+Ly6G−Ly6Chi) and Granulocyte-MDSCs (G-MDSCs, CD11b+Ly6G+Ly6Clo) ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation